2023
DOI: 10.3389/fpsyg.2023.1124235
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the validity of the Head-Toes-Knees-Shoulders task in predicting young children's academic performance

Sabrina Ann Kenny,
Claire E. Cameron,
Jasmine Tua Karing
et al.

Abstract: The present study represents the first meta-analytic synthesis of the utility of a widely used early-childhood self-regulation measure, the Head-Toes-Knees-Shoulders task, in predicting children's academic achievement. A systematic review of the literature yielded 69 studies accessed from peer reviewed journals representing 413 effect sizes and 19,917 children meeting the complete set of inclusion and exclusion criteria. Robust variance analysis demonstrated that the Head-Toes-Knees-Shoulders task was a consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Given the cultural-embeddedness of self-regulation and its assessment, broadening the socio-demographic characteristics of children given HTKS-Kids is perhaps the most important. It is promising that the HTKS has been translated into 28 languages and used worldwide, and a meta-analysis indicated no differences in how well HTKS predicted young children's academic achievement by country or cultural context (Kenny et al, 2023 ). Collecting data with a larger sample of racially diverse children can help establish whether HTKS-Kids could mitigate implicit bias against Black children, which may contribute to the differences we found in teacher ratings of children's classroom self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cultural-embeddedness of self-regulation and its assessment, broadening the socio-demographic characteristics of children given HTKS-Kids is perhaps the most important. It is promising that the HTKS has been translated into 28 languages and used worldwide, and a meta-analysis indicated no differences in how well HTKS predicted young children's academic achievement by country or cultural context (Kenny et al, 2023 ). Collecting data with a larger sample of racially diverse children can help establish whether HTKS-Kids could mitigate implicit bias against Black children, which may contribute to the differences we found in teacher ratings of children's classroom self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the initial variability and range in scores for Brazilian and US adolescent children on the HTKS, a well-validated measure of EF used in preschool and kindergarten populations. We also expanded past work with the HTKS (e.g., McClelland et al, 2014 ; Kenny et al, 2023 ) by creating an efficiency score, reducing the potential ceiling effects found with older populations. Results indicated that there was sufficient variability and range in HTKS efficiency scores, with the Brazilian and US sample scoring at the ceiling for only 2 and 4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Head-Toes-Knees-Shoulders (HTKS) task is a brief and easy-to-administer measure of EF that has been extensively used with preschool and kindergarten-age children ( Cameron Ponitz et al, 2007 ; McClelland et al, 2014 ; Kenny et al, 2023 ). The HTKS demonstrates strong reliability and validity ( McClelland et al, 2014 ) and is related to academic and health-related outcomes during early childhood ( Cameron Ponitz et al, 2009 ; Becker and Nader, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these earlier researches did not take into account the broader notion of self-regulation because they solely looked at behavior regulation. Both behavior regulation and emotion regulation are included in the idea of self-regulation, and both are linked to children's academic success [94,95]. Consequently, it is crucial to understand the emotion regulation and contribution of behavior to gender differences in academic school achievement.…”
Section: Academic Performancementioning
confidence: 99%